2018
DOI: 10.4172/neuropsychiatry.1000363
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the TAM Family of Receptor Tyrosine Kinases in Neural Development and Disorders

Abstract: Tyrosine kinase receptor 3 (Tyro3), Axl, and Mer constitute the TAM family of receptor tyrosine kinases. These receptor tyrosine kinases are characterized by a conserved sequence within the kinase domain and adhesion molecule-like extracellular domains. The TAM family and their shared ligands, growth arrest-specific gene-6 (Gas6) and protein S, are differentially expressed in the developing and adult nervous systems. The TAM family regulates normal cellular processes and plays an important role in nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…6,9 The TAM receptor family regulates normal cellular processes and plays important roles in the nervous system development and diseases, specifically in cell proliferation/survival, cell adhesion and migration, neuronal differentiation, cell apoptosis, myelination, degeneration, and immune regulation. 6,9 However, it is not known whether TAM is involved in peripheral mechanisms of neuropathic pain. In a previous study by our group, RNA-Seq analysis of spinal nerve-ligated DRGs demonstrated a significant increase of AXL mRNA in injured L4 DRG in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9 The TAM receptor family regulates normal cellular processes and plays important roles in the nervous system development and diseases, specifically in cell proliferation/survival, cell adhesion and migration, neuronal differentiation, cell apoptosis, myelination, degeneration, and immune regulation. 6,9 However, it is not known whether TAM is involved in peripheral mechanisms of neuropathic pain. In a previous study by our group, RNA-Seq analysis of spinal nerve-ligated DRGs demonstrated a significant increase of AXL mRNA in injured L4 DRG in mice.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 S-AXL binds Gas6 and acts as a ligand sink to inhibit the normal cellular functions of full-length AXL receptor. 5,6 Recent clinical studies have indicated that AXL might also be involved in pathological pain. One study showed that both s-AXL and GAS6 concentrations were increased in critical limb ischemia patients and correlated with levels of C-reactive protein, interleukin-6, tumor necrosis factor alpha, and neopterin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RTKs regulate several cellular processes, including cellular growth, differentiation, proliferation, motility, and apoptosis in multiple organs and systems [1]. The TAM receptor subgroup has received growing attention due to the crucial role in the preservation of homeostatic balance through the modulation of immune, nervous, vascular, and reproductive functions [26].…”
Section: Introductionmentioning
confidence: 99%
“…The role of TAM receptors and their ligands in cell proliferation, survival, and migration is vital in neural development and myelination (reviewed in [ 70 ]). Upon activation of Axl, Grb2 and SOS are recruited, which leads to the activation of ERK, cell migration and proliferation [ 71 ].…”
Section: Biological Functionsmentioning
confidence: 99%